Virtual testing of aluminum and Nomex® honeycomb core structures using ls-dyna and Python/SeabornAlparslan - Solak, Alparslan; Ascioglu Temiztas, Birgul; Bolat, Berna (YILDIZ TECHNICAL UNIV, 2022)
Honeycombs are essential elements in mechanical systems where low weight and high strength are required. Aluminum and Nomex (R) are the most commonly used honeycomb materials in structures exposed to compression stress. The primary purpose of this study is to verify the compression behavior of honeycombs in Ls-Dyna using experimental values and theoretical equations. Additionally, it is aimed to evaluate the honeycombs parameters such as cell diameter, cell wall thickness, and material. A correlation matrix was created using the Python/Seaborn program to examine the impact coefficients of the parameters. In this way, the effect of design parameters on compression strength and internal energy was investigated.
Keywords: Compression; Honeycomb; Aluminum; Nomex (R); Ls-Dyna; Python/Seaborn; SANDWICH PANELS; CRASHWORTHINESS ANALYSIS; Engineering